Voluntary Peer Review on Consumer Protection Law and Policy - Peru - United Nations Conference on Trade; Development (United Nations, 2020)
Voluntary peer reviews provide an expert and independent assessment of the effectiveness of the consumer protection right in a given country; analyze the legislative, institutional and public policy frameworks, together with the application of the law, in order to determine the difficulties to be faced and the areas that can be improved in the legal and institutional frameworks; assess the degree of awareness of relevant stakeholders about consumer protection, as well as their contributions in this area; formulate and recommend appropriate measures; and assist implementation of relevant recommendations by developing a capacity-building programme.